Understanding Instructional Communication towards Elementary School Students in English Classroom - Ummi Kultsum; Siti Zulfa; Lulu Farhan; Vivi Savitri; Atiq Susilo (Universitas Pendidikan Ganesha, 2023)
English teachers and students face difficulties grasping the meaning, leading to misunderstanding. This study aims to analyses the use of conversational implicature focusing on instructional communication in an English classroom. The research used qualitative methodology and descriptive analysis as the design. The instrument consisted of observations and documentation. The research data used video recording during an English classroom process. The participants of this study involved an English teacher and students in grade 5 at an Islamic private elementary school. This study used an interactive analysis model consisting of collection, reduction, conclusion and verification. This study indicated that English teachers and students used the four maxims of conversational implicature focusing on instructional communication, with 18 utterances. The maxim of quantity consisted of 3 utterances. The maxim of relation consisted of 5 utterances. The maxim of manner consisted of 4 utterances. The most dominant conversational implicature was the maxim of quality consisting of 6 utterances. It showed that the interaction between English teachers and students needs to provide factual and accurate information. Therefore, it becomes necessary for English teachers and students to understand the language's meaning in instructional communication by involving the conversational implicature or four maxims, particularly in elementary school.